FMEA and AHP Methods in Managing Environmental Risks in Landfills: A Case Study of Kahrizak, Iran - Benyamin Sadeghi; Mansour Sodagari; Hossein Nematollahi; Hamed Alikhani (Environmental Energy and Economic Research, 2021)
As waste disposal centers are the hub of pollutants, the emission of these pollutants and their byproducts such as smell and dust, which are produced during the disposal process, may cause public grievances over waste disposal. The daily production of more than 8,000 tons of urban waste in Tehran has caused problems for the Tehran municipality. The Kahrizak landfill in Tehran has weaknesses, which leads to risks and citizens' discontentment as well as environmental issues and hazards. Due to population growth in megacities and the per capita increase in waste production, the need for a more suitable landfill has been one of Tehran's officials' concerns. In this study, after identifying risks at Kahrizak using a survey, the failure mode and effects analysis (FMEA) method and analytic hierarchy process (AHP) are integrated to prioritize these risks. After the distribution of a questionnaire among 130 waste management experts, 22 risks were identified. Then, with the scoring of the risk severity, the probability of occurrence, and the detectability potential, the risk priority number (RPN) was calculated, and the risks were prioritized based on RPN. The results show that the following risks had the highest priority: change in land use, distance to the city limits signs, and distance to the airport. Finally, nine corrective actions were identified in a follow-up survey, which was distributed among 92 experts, to address the landfill’s risks in Tehran and other similar megacities.